Kontribusi Seesaw sebagai assesment for learning dalam mengukur keterampilan berpikir abad 21 - Fadilah, Eva; Wulan, Ana Ratna; Diana, Sariwulan (Assimilation: Indonesian Journal of Biology Education, 2020)
The 21st Century thinking skills are important skills to have for everyone. These skills can be developed through learning and assessment with the help of applications. This study aims to measure 21st century problem solving skills using Seesaw as an assessment for learning. The method used is descriptive. This research was conducted in one class 10 of SMAN X in West Bandung which was selected by purposive sampling. This study used three project based learning projects. The instruments used were tasks, test instruments, and questionnaires. The task is uploaded in the Seesaw application and assessed with a rubric which is modified from the K-12 Public Education standard 2015. The test instrument is adapted from the NAEP (National Assessment of Educational Progress). The results showed that there was an increase in students' problem solving skills with more N-gain scores in the high category. The mastery of problem solving skills was more in mastery. The progress of students' problem-solving skills also increased during the completion of task 1 to task 3.